Quality of Work-Life Among Workers in Multinational Companies: Does Organizational Climate, Organizational Safety and Workplace Stress Counts? - Enyelunekpo R. Roberts; Helen M. Diri; Ayotunde A. Oyinlola; Emmanuel E. Uye (Cita konsultindo, 2026)
Quality of work-life has continued to dominate research as it is known to affect workers’ performance and organizational productivity. Studies have investigated different predictors of quality of work-life with different results. This study examines organizational climate, organizational safety and workplace stress as predictors of quality of work-life among workers in multinational companies in Rivers State, Nigeria. Cross-sectional survey design was adopted while purposive sampling technique was used to select two multinational companies in the study area. Data were collected from 207 participants using validated questionnaires. Data were analyzed using multiple regressions and independent samples t-test to test two hypotheses which were accepted at p <.001 level of significance. The result indicated that organizational climate, organizational safety and workplace stress jointly predicted quality of work-life among study participants R2 =.398, F( 3, 204) = 124. 461, p < .001. Furthermore, the results revealed that organizational climate (β = .105, p <.001), organizational safety (β= .164, p <.001) and workplace stress (β = -.129, p <.001) independently predicted quality of work-life among study participants. Finally, gender significantly influences quality of work [t(107) = 44.48, p <.001] such that female workers reported higher quality of work-life compared to their male counterparts. The study concludes that organizational climate, organizational safety and workplace stress served as excellent predictors of quality of work-life among study participants. The study recommends that multinational companies should develop positive organizational culture and workplace safety with minimal workplace stress which would improve overall quality of work-life among workers.